Acute phase proteins in patients with psoriasis - Korczowska, Izabela; K. Łącki, Jan; Olek-Hrab, Karolina; Żaba, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
Psoriasis is a chronic inflammatory cutaneous disease with a population prevalence of 2%-3% in North America and most European countries. One of the form is psoriatic arthritis which affects up to 10% of patients with skin psoriasis. The pathogenetic connection between psoriasis and arthritis is not clear. In both disorders there is an increased concentration of proinflammatory cytokines such as tumor necrosis factor (TNF- -alpha) and acute phase proteins. The aim of the study was to investigate relations between concentration and glycosylation pattern of serum acute phase proteins, and clinical appearance in psoriasis and psoriatic arthritis patients. We investigated a group of 49 patients (16 women, 33 men) with mean age of 41 years with psoriasis and psoriatic arthritis. In all patients Psoriasis Area Severity Index (PASI) was assessed. Serum levels of C-reactive protein (CRP), AGP, ACT, transferrin, and C3 and C4 complement components were measured using affinity electrophoresis, whereas glycosylation of a1-acid glycoprotein (AGP) and alpha-chymotrypsin (ACT) was measured using affinity electrophoresis with concanavalin A (con-A); the results were expressed as reactivity coefficients (AGP-RC, ACT-RC). Serum levels of TNF-alpha were estimated using ELISA. Our data show a good correlation between some of the acute phase protein response and skin involvement.